Being Digitally Wise: Literature Study - Maharani, Okvi; Maharani, Rizna; Ningsih, Wulandari; Catur Wahyuni, Hana; Fariyatul, Eni (Annpublisher, 2023)
The rapid development of digital technology affects various aspects of human life,including education, economy, and communication. However, these changes also bring newchallenges, such as the spread of false information, vulnerable privacy, and inequality of access totechnology. Wise digital literacy is an urgent need in facing this challenge. Digital literacy meansknowing, the skills to understand, evaluate, and use digital information wisely. In the 4.0 era, digitalliteracy skills are an important skill for all individuals, not only for those who are actively involvedin technology. This research aims to be able to prepare students as the next generation of the nationso that they are wise in using digital-based media. The method used is by Systematic LiteratureReview (SLR). The results of this study show that many factors influence the wise use of digitalmedia, namely the need for family, school, and community support in optimizing the use of digitalmedia. Strengthening character education and continuous mentoring is one example that can beimplemented in the school environment.